FREQUENT OCCURRING FORMS OF INTERNET FRAUDS (Heritage, 2022)
The increase in the volume of electronic transactions has led to the need to strengthen data protection against criminal activities in the online environment. The author emphasizes that the perpetrators’ goal is of a lucrative nature, might be gotten by disrupting the information system too, as well as offenders can be both individuals and legal persons. The profile of a cybercrimе criminal, in general, implies excellent knowledge of digital proceedings, experience of acting in the online environment and active performing of information technology skills. The Internet has become an integral part of today's way of life, which is why the scope of criminal activities in this worldwide network for communication and data exchange is constantly expanding. The author deems this as the reason for the growing need to strengthen information security, which he determines as the practical implementing of measures to protect data from external influences in the online environment. This paper presents a statistical analysis of the Internet frauds’ frequency from 2016 to 2020, in order to show the real intensity of this modern kind of criminal threat.
Keywords: Internet, Internet frauds, online environment, cybercrime, information system, information security, cybercrime threat